Implementasi Ekstrakurikuler Pramuka dalam Membangun Karakter dan Prestasi SDN 1 Watukelir, Kecamatan Ayah, Kabupaten Kebumen - Ema Kurnia Winanti; Agung Nugroho (Journal on Education, 2024)
Contemporary education emphasizes not only classroom learning but also the cultivation of character and achievement through extracurricular activities. Scouting is one such mandatory extracurricular activity for students. This study aims to investigate the implementation of the scouting extracurricular program in developing students' character and achievement at SDN (Public Elementary School) 1 Watukelir. The research design employed is descriptive research. Observation, interviews, and documentation were used to collect data. The subjects of this study comprised the school principal, scout leaders, classroom teachers, students, and parents. Data validity was ensured through triangulation of techniques and sources. The findings indicate that character development and achievements can be fostered through the scouting extracurricular program. This is evidenced by the program's effectiveness in instilling traits such as discipline, independence, and responsibility, as well as achievements in scouting activities up to the provincial level. The school's efforts in student regeneration contribute to early positive transformations among students and stabilize school achievements.